Hubungan Pengetahuan Remaja Putri tentang Kanker Payudara dengan Perilaku Pemeriksaan Payudara Sendiri - Laily Prima Monica (Journal of Ners and Midwifery, 2016)
Breast cancer is an important health problem. The frequency of breast carcinoma in developed countries was the highest by a ratio of 5: 3 compared with breast carcinoma in developing countries. In Indonesia, breast self examination become the trending topic but still canot take public attention so that the behaviour of breast self examination only be done by small number of people. The study investigated the correlation between knowledge on breast cancer and the behaviour of breast self examination of adolescent’s. This was an analytic study with a cross-sectional research design. The location was selected in Blitar. The sampling was done by proportional sampling technique. The sample was 52 students. The instrument used analyzed chi-square test. The result showed that from the 52 respondents, 1.9% of respondents had good knowledge and good behavior on breast self-examination, 3.85% of the respondents had good knowledge and enough behaviour on breast self-examination, 25% of respondents had good knowledge and less behaviour on breast self-examination, 3.85% of respondents good knowledge and not good behaviour on breast self-examination. Through the data analysis obtained X2> X2 table, this means that there was a significant correlation between the knowledge of young women about breast cancer and breast self-examination behavior. Knowledge of young women is influenced by internal and external factors that can cause changes in a person’s behavior.